2020
DOI: 10.1038/s41598-020-69488-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived ovarian cancer organoids capture the genomic profiles of primary tumours applicable for drug sensitivity and resistance testing

Abstract: The use of primary patient-derived organoids for drug sensitivity and resistance testing could play an important role in precision cancer medicine. We developed expandable ovarian cancer organoids in < 3 weeks; these organoids captured the characteristics of histological cancer subtypes and replicated the mutational landscape of the primary tumours. Seven pairs of organoids (3 high-grade serous, 1 clear cell, 3 endometrioid) and original tumours shared 59.5% (36.1-73.1%) of the variants identified. Copy number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
118
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 34 publications
3
118
0
1
Order By: Relevance
“…Most importantly, the drugs identified were validated in vivo with matched PDTX models, providing proof-of-concept that the patient-derived organoids can be utilized for complete genomic analysis together with high-throughput drug screening of a comprehensive up-to-date library [ 98 ]. Similarly, several other studies have shown that tumor organoids and spheroids can be utilized for anti-cancer drug screening [ 18 , 19 , 21 , 54 , 56 , 92 , 94 , 96 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Applications Of Patient-derived Organoids and Spheroidsmentioning
confidence: 95%
“…Most importantly, the drugs identified were validated in vivo with matched PDTX models, providing proof-of-concept that the patient-derived organoids can be utilized for complete genomic analysis together with high-throughput drug screening of a comprehensive up-to-date library [ 98 ]. Similarly, several other studies have shown that tumor organoids and spheroids can be utilized for anti-cancer drug screening [ 18 , 19 , 21 , 54 , 56 , 92 , 94 , 96 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Applications Of Patient-derived Organoids and Spheroidsmentioning
confidence: 95%
“…Compared to the classical 2D cancer cell lines, organoids are more difficult to operate and more expensive to maintain. However, they represent more reliably the pathological features of the tumor, as PDOs maintain genetic stability and tumor heterogeneity [6,[8][9][10][67][68][69][70][71][72][73][74], which instead are lost during the long-term selection required to establish 2D tumor cell lines. In comparison with patient-derived xenografts (PDXs) or genetically engineered animal models, PDOs are less time consuming, less expensive and more appropriate for high-throughput drug screening.…”
Section: Patient-derived Organoidsmentioning
confidence: 99%
“…In comparison with patient-derived xenografts (PDXs) or genetically engineered animal models, PDOs are less time consuming, less expensive and more appropriate for high-throughput drug screening. Furthermore, PDOs are usually obtained with higher success rate than PDXs and can also be formed from non-transformed cell cultures or preinvasive cancer models [6,[8][9][10][67][68][69][70][71][72][73][74]. Lastly, with respect to spheroids, which are clusters of proliferating cells that assemble in 3D sphere-like structures floating in the culture medium [75], PDOs offer a better representation of the architecture of the tumor, as they assemble onto a reconstituted matrix that resembles the basal lamina of epithelia and recapitulate the cellular heterogeneity of the tumor mass.…”
Section: Patient-derived Organoidsmentioning
confidence: 99%
See 2 more Smart Citations